TECHNICAL EFFICIENCY OF OFFSHORE SUPPLY VESSEL ACCIDENT: A PARAMETRIC APPROACH - MOKHTAR, KASYPI; BAHAR, FITRI AL-AZIZI; MHD RUSLAN, SITI MARSILA; ABU BAKAR, ANUAR; BIN, LOKE KENG; ISMAIL, MOHD RIZAL; ABDUL HALIM, WAN ZULHILMI (Journal of Maritime Logistics, 2023)
This study intended to measure accident rates based on human element since major accidents has led to large number of fatalities in shipping industry. For that purpose, Data Envelopment Analysis (DEA) is applied to test both cross sectional and panel data for each Decision-Making Unit (DMU). Additionally, this study used DEA-CCR model as well as variable method and the return to scale method (RTS) to provide a more comprehensive outcome. From the result, it is found that 5 vessels are efficiently operated, while 30 vessels are under-efficient. As a consequence, these 30 vessels need to revise their SOP on safety and current policies to boost their safety performance and awareness. Only from that, the vessels could reduce the occurrence of accident and able to operate efficiently and systematically.